Sex‐dependent age trajectories of subcortical brain volume: A UK Biobank study (N=39, 544). (December 2021) - Ching, Christopher; Muir, Alexandra M; Santhalingam, Vigneshwaran; Abaryan, Zvart; Zhu, Alyssa H; Thomopoulos, Sophia I; Jahanshad, Neda; Thompson, Paul M
Abstract: Background: Understanding the normative variation in brain structure across life may provide insights into healthy aging as well as neurological disorders such as Alzheimer's disease (AD). Women are at greater risk of developing AD, but men tend to show faster rates of subcortical atrophy across adulthood. Sex‐dependent differences in male and female brain aging trajectories may change over the adult lifespan, and could play a role in differential risk for neurological illness. The current study maps normative trajectories (nomograms) of subcortical volume across adulthood and quantifies the interaction between age and sex in a large, healthy sample. Method: T1‐weighted brain MRI from a sample of UK Biobank participants free from psychiatric/neurological illness (; N=39, 544; 44.6‐82.8 years) were segmented using FreeSurfer 7.1 to derive average left and right thalamus, putamen, pallidum, hippocampus, amygdala, caudate, nucleus accumbens and ventricle volumes. Normative quantile regression models (nomograms) were created to visualize aging trajectories for each volume. Linear mixed models were fit in binned age groups to assess age‐by‐sex interactions across middle to late adulthood. Result: Nomograms showed volumetric loss across adulthood, except for ventricular volume which was larger with increasing age (). Compared to females, males showed a steeper slope of volume change with increasing age in all regions across the full age range (Cohen's d : ‐0.14 ‐ 0.12) (). Binned‐age analysis showed males to have steeper volume loss trajectories in middle adulthood, with fewer age‐by‐sex interactions detected later in life for most structures. Conclusion: In a large sample of healthy adults, we found a structure‐specific interaction between age and sex, with males tending to show steeper age‐related volume loss trajectories compared to females until later decades of life, where trends appeared similar for men and women. This study provides normative subcortical aging trends and identifies potential sex‐dependent variations across life that may be used to understand healthy brain aging and risk for disorders such as AD.